Physico-Chemical Investigation And Biological Studies Of Metal Complexes With 2-[N-(3,4-Dimethoxy-2-Hydroxyphenyl)–Methylidinyl]-Amino-4, 5 Dihydronaphtho[1,2d]-Thiazole - VIJAYKUMAR DURG; NIRDOSH PATIL; K.H. SHIVAPRASAD (International Journal of Pharma and Bio Sciences, 2011)
Condensation of substituted salicylaldehydes with primary amine of naphtha-thiazole gave a of Schiff base, such as 2-[N-(3,4-dimethoxy-2-hydroxyphenyl)–methylidinyl]-amino-4, 5-dihydronaphtho[1,2d]-thiazole (HL); Complexes were synthesized by reaction between cobalt chloride, nickel chloride and copper chloride with the ligand (HL). These complexes were characterized by elemental analyses, conductance measurements, magnetic susceptibility measurements, IR, 1H NMR, and electronic spectral studies. On the basis of magnetic and spectral studies, octahedral geometry was assigned for these complexes. These complexes have been screened in vitro for their possible antimicrobial activity